Cognitive Distortion While Attending Online Class: Study on Banjar College Student - Rudi Haryadi; Aminah Aminah; Sri Ayatina Hayati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Online learning has begun to take place in Indonesia since March 2020 simultaneously in all educational institutions due to the outbreak of the Covid-19 outbreak. Sudden changes make it difficult for students to process information and lead to various patterns of thinking errors which are known as cognitive distortions. This study aims to reveal the patterns of cognitive distortions that students have during the online lectures. The research design used is a phenomenological qualitative design. Analysis of cognitive distortions was collected through in-depth interviews and document studies to 8 Banjar ethnic students. The results of the study found that there were 3 cognitive distortions, namely: (1) catastrophizing; (2) all-or-nothing thinking; and (3) should statements. The effects of these cognitive distortions include feeling lazy, bored, afraid, uncomfortable, drowsy, shaking, and heart palpitations. In the context of student behavior, students also tend to neglect lectures, access social media, sleep, and go to hang out with friends. Further research is needed to explore student’s cognitive distortions in post-Covid-19 pandemic situation or with diverse populations.